The Role of Fiscal Policy Rating Variables on Economic Growth in the LDCs - António Afonso; M. Carmen Blanco-Arana (CESifo GmbH, 2024)
We assess empirically the role of the World Bank's Country Policy so-called fiscal policy rating variables (fiscal rating, debt rating and revenue rating) on economic growth in the 46 Least Developed Countries (LDCs) in the world, during the period 1990-2022. We also investigate the role of key fiscal variables on economic growth (government debt, expenditure and tax revenue). The empirical evidence suggests that better fiscal policy rating strongly and positively affects economic growth. We also find that the influence of government debt and tax revenue can contribute to influence economic growth. Results are robust by applying a fixed effects model and GMM model.
Keywords: C23; G10; O10; O43; 330; economic growth; LDCs; fiscal policy; fixed effects model